KEBERTERIMAAN MEDIA PEMBELAJARAN BERBASIS WEBSITE “ALAT GERAK HEWAN DAN MANUSIA” DENGAN ALUR MERDEKA DI SEKOLAH DASAR WILAYAH BANTEN - safitri, safitri; Dede Tri Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of technology in the learning process in schools is currently often used to support teachers in teaching. The use of technology in education by teachers in elementary schools can enrich students' learning experiences, so it is important for teachers to use technology as a tool in learning. Web-based learning media is one form of technology utilization in education, which is implemented in the teaching and learning process using technology. Research on the use of website-based learning media has received a good response, and researchers will research the acceptance of Website-Based Learning Media with the Merdeka Flow Model (Starting from self, Elaboration, Collaboration Space, Demonstration and Real Action) by teachers throughout Banten. This research was conducted using a quantitative research approach. The research method used by researchers is a correlational survey with path analysis. The results of the study show that the creation of website-based digital media with a free flow in the Banten region was well received, this can be seen from the results of Self-Efficacy (Self-Application) which has a relationship with Behavioral Intention (Technology Acceptance) which has good acceptance seen from the value above that the response results related to these indicators are influenced by self-influence and efforts to use media which are the main determinants in the acceptance and effectiveness of learning media.